A cosmic ray test platform based on high time resolution MRPC technology - 陈天翔 李澄 孙勇杰 陈宏芳 邵明 唐泽波 杨荣星 周意 张一飞 (Chinese physics C, 2015)
In order to test the performance of detector prototypes in a laboratory environment, we design and build a large area （90 crux52 cm） test platform for cosmic rays based on a well-designed Multi-gap Resistive Plate Chamber （MRPC） with excellent time resolution and a high detection efficiency for minimum ionizing particles. The time resolution of the MRPC module used is tested to be -80 ps, and the position resolution along the strip is -5 mm, while the position resolution perpendicular to the strip is -12.7 ram. The platform constructed by four MRPC modules can be used for tracking cosmic rays with a spatial resolution of -6.3 mm, and provide a reference time -40 ps.